If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x-5(-x-9)=39
We simplify the equation to the form, which is simple to understand
-4x-5(-x-9)=39
Reorder the terms in parentheses
-4x+(+5x+45)=39
Remove unnecessary parentheses
-4x+5x+45=+39
We move all terms containing x to the left and all other terms to the right.
-4x+5x=+39-45
We simplify left and right side of the equation.
+1x=-6
We divide both sides of the equation by 1 to get x.
x=-6
| 2(y-5)-2x-y=7 | | 2X-3/4=-1/10 | | X=2x^2-5x+2 | | 13-4=6 | | 2(x-4)=3(x-1) | | 2a-4=10a | | 5a+3+6a-12+90=180 | | 11-5=5 | | .7(200-x)=126 | | 7(y+4)=3y-8 | | x+50=180 | | 8[4-(-4x-9)]=64x+176 | | .7(200-x)=133 | | solve(2+4)(2-2)=-5 | | 3(12-5)^2/(4+3) | | -2.1q-1=6.6 | | -4U+3/2=7/2U-1/5 | | 4+2x+15=x+13 | | 12x+25=29 | | 5a+3+6a-12=180 | | 4.7+3g=7.3 | | sqrt(5-x)+1=x-2 | | 4.2(x+8.7)=8.7x | | -4-n-4=-11 | | 6-x=37 | | 12x-1+3=7x+1 | | 3a/2+1=18 | | 22/5d*10/2 | | 3-4q=10+10 | | 3a+6+4a=-36 | | x+11=2x-7 | | 5-9/2d=33 |